MODEL MATEMATIS PERSEDIAAN TERINTEGRASI ANTARA SUATU PERUSAHAAN DAN DISTRIBUTORNYA - Nyoman Sutapa; Fransiska Fransiska (Institute of Research and Community Outreach - Petra Christian University, 2000)
Two mathematical model of inventories are analised. The aim of these models are minimizing the total cost of inventories on a company and its distributor. The first mathematical model is IDQ (Identical Delivery Quantity) model, i.e. the amount of delivery to distributor is identically for every replenishment. The second one is DWP (Delivery What is Produced) model, i.e. the amount of delivery to distributor is not identically for every replenishmen, all of distributor's inventories are supplied to distributor. Both of these models, handling the coorporation of inventory control between company and one distributor. At the end of this paper, will be showed a numerical example and from it will be analized in which situations one of these models is the best. Abstract in Bahasa Indonesia : Dua buah model matematis persediaan terintegrasi dianalisis. Kedua model bertujuan untuk meminimumkan total biaya persediaan dari sebuah perusahaan dan distributornya yang saling terkoordinasi dan bekerjasama. Model matematis tersebut adalah model IDQ (Identical Delivery Quantity), jumlah pengiriman produk kepada distributor adalah sama pada setiap pengiriman, dan kedua adalah model DWP (Delivery What is Produced), jumlah pengiriman kepada distributor adalah bervariasi pada setiap pengiriman, yaitu semua persediaan yang tersedia pada perusahaan saat itu dikirim ke distributor. Pada bagian akhir dari makalah ini akan ditampilkan sebuah contoh numeris, yang daripadanya akan diperlihatkan dalam keadan bagaimana sebaiknya satu diantara kedua model dipilih. Kata kunci: model matematis, persediaan, terintegrasi.